Semangat merdeka - Jabatan Kebudayaan dan Kesenian Negara (Kuala Lumpur : Jabatan Kebudayaan Dan Kesenian Negara, 2005)
Documentary on history of the struggle for independence of Malaya/Malaysia.
Keywords: Independence Day (Malaysia).; Malaysia -- History; Malaysia -- Politics and government